Case Report on Carcinoma Mammae Patient with Readiness to Improve Religiosity Problem - Susanti, Indah; Andini, Amelia (Global Indonesia Health Care (GOICARE), 2024)
Background: Palliative care is the care of a patient and their family who have an incurable disease by improving the patient's quality of life and reducing disturbing symptoms spirituality and religiosity are important components in the palliative care of cancer patients which are important aspects of cancer patient care. can improve the quality of life and reduce the suffering of cancer patients. Purpose: To determine the benefits of palliative nursing from spiritual/religious aspects in the case of Carsinoma Mammae patients in the Cendana 2 room of Dr. Sardjito Hospital Yogyakarta. Methods: Case study research on patients with Carcinoma Mammae totaling 2 people. Data collection techniques are observation and interviews. Results: In case 1 and case 2, the priority nursing diagnosis of readiness to improve religiosity was taken and nursing care was carried out for 3x24 hours. The implementation given is using therapeutic communication in building a trusting relationship, asking the patient's feelings, conducting spiritual assessments, encouraging participation related to family and other people's involvement, providing privacy / quiet time for spiritual activities, encouraging the use of spiritual resources. Conclusion: The results of evaluating nursing care readiness to improve religiosity on the third day of case 1 (ability to worship) and case 2 (ability to worship and pray) have not been resolved. Conclusion: Patients are expected to be able to implement routine worship activities in daily life and can increase religiosity in the face of palliative disease.